Combining ability and heterosis studies for grain iron and zinc concentrations in pearl millet [Cenchrus americanus (L). Morrone] - Thribhuvan, R.; Singh, S. P.; Sankar, Mukesh S.; Singh, Anju M.; Mallik, M.; Singhal, Tripti; Meena, Jitendra Kumar; Satyavathi, C. Tara (Frontiers in Plant Science, 2023)
Iron and zinc deficiency has been identified as a major food-related health issue affecting two billion people globally. Efforts to enhance the iron (Fe) and zinc (Zn) content in food grains through plant breeding is an economic and sustainable solution to combat micronutrient deficiency in resource-poor populace of Asia and Africa. Pearl millet, Cenchrus americanus (L). Morrone considered a hardy nutri-cereal, is the major food crop for millions of people of these nations. As an effort to enhance its grain mineral content, an investigation was conducted using line × tester analysis to generate information on the extent of heterosis, gene action, combining ability for grain yield potential and grain mineral nutrients (Fe and Zn). The partitioning of variance attributable to parents indicated that the lines and testers differed significantly for the traits studied. For most of the attributes, hybrids which were superior to the parents in the desired direction in terms of per se performance were identified. The analysis of combining ability variance indicated the preponderance of both additive and non-additive genetic effects. Thus, reciprocal recurrent selection can be used to develop a population with high grain Fe and Zn contents. The Fe and Zn content in grain exhibited a highly significant and positive association between them, whereas the Fe and Zn contents individually showed negative, albeit weak, correlation with grain yield and moderate positive relation with grain weight. This indicates that mineral nutrient contents in grains can be improved without significant compromise on yield. The consistency of these trends across the environment suggests that these findings could be directly used as guiding principles for the genetic enhancement of Fe and Zn grain content in pearl millet.